Perceived Source of Stress and Associated Stressors among Medical and Dental Students of in a Medical College of Chitwan - Bhattarai, Rosina; Pandey, Anisha; Roy, Prabhas; K.C, Sweta (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Medical and dental students are subjected to high level of stress whether academic, social or health related. Stress in manifested as fatigue, tension, dizziness, inability to fall asleep, irritation, anxiety, suicidal thoughts thereby degrading their quality of life. Therefore, this study was conducted with an objective of assessing perceived stress, stressors and the severity of the stressors. Methods: A cross-sectional study was conducted among 272 medical and dental students of College of Medical Sciences. Perceived Stress Score (PSS) scale with 10 items questions was used for identifying perceived stress. 32 potential stressors whose severity was rated using Likert scale using score 1 for never/rarely, score 2 for sometimes and score 3 for often/always was used. Ethical clearance was obtained from College of Medical Sciences Teaching Hospital - Institutional Review Committee. Results: Using mean of PSS score, it was found that 74.26% of the students were stressed. Statistically significant difference was found between gender and stress score. The most frequently occurring academic stressors was reported to be performance in examination (37.9%). Similarly, the most commonly occurring psycho-social stressors was found to be relation with opposite sex (44.5%) which covered the greatest percentage among all stressors. Conclusions: A large proportion of students in both dental and medical studies are experiencing stress especially on academic and psycho-social aspects. All the stressors must be addressed and students should be taught stress management techniques.